PERILAKU PENANGANAN NYERI DISMENORE PADA REMAJA DI SMP PGRI 5 DENPASAR: DYSMENORRHEA PAIN MANAGEMENT BEHAVIOR IN ADOLESCENTS IN SMP PGRI 5 DENPASAR - Fredelika, Lili; Oktaviani, Ni Putu Wiwik; Suniyadewi, Ni Wayan (Stikes Wira Medika Bali, 2020)
Problems that arise during menstruation such as dysmenorrhea are problems that are often experienced by 30-50% of young women in each country. The high incidence of dysmenorrhea is not matched by good behavior, where documentation is still rarely found by adolesence in School Health Unit. Proper knowledge, attitudes and actions are needed to create good behavior. The aim of this study is to determine the handling of dysmenorrhea pain in adolescents at SMP PGRI 5 Denpasar. The method used is descriptive quantitative with cross sectional approach. Data collection techniques using a questionnaire, while the sampling technique using probability sampling with stratified random sampling technique, the number of samples as many as 154 students of class IX. The results showed 116 students (75.3%) had good knowledge, 110 students (71.4%) had good attitudes, 139 students (90.3%) had less dysmenorrhea treatment measures. So it was concluded that the behavior of pain handling dysmenorrhea in adolescents in SMP PGRI 5 Denpasar included in the sufficient category (91.5%). It is hoped that this study can improve the behavior of pain handling dysmenorrhea in adolescents. The better the level of knowledge, attitudes and actions shown by adolescents, the better the behavior of dysmenorrhea pain management in adolescents.